(untitled) (Research, Society and Development, 2020)
Vitamin D is a mineral vitamin supplement, whose function is related to bone health, also responsible for other activities, regulates growth, immune system, cardiovascular, muscles, metabolism and insulin, maintaining the proper concentrations of calcium and phosphorus in the body. When combined with other micronutrients, vitamin D becomes fat-soluble, acquired through food and sunlight. The main diseases caused by lack of vitamin D were evaluated, noting that excessive consumption can cause serious problems, such as obesity, already lacking malnutrition. From the studies analyzed, it can be concluded that vitamin D bioavailability is associated with regulation and maintenance for a healthy life. This study exposes the need for maintenance of vitamins for maintenance, presenting the importance of supplementation for people over 65 years and pregnant women.